Examining the Relationship between Chinese EFL Learners’ Self-Perceived Impression of Oral Presentation Performance and Foreign Language Anxiety - Liu, Shuang (Journal of Education and Learning Environments, 2025)
Foreign language anxiety as an influential determinant of foreign language achievement has long been receiving attention by scholars and educators. However, few studies have investigated how specific components of self-perceived oral presentation performance associate with foreign language anxiety. Additionally, how personality traits would moderate the relationship between self-perceived oral presentation performance and foreign language anxiety remains unexplored. This quantitative study aims to investigate the association between self-perceived oral presentation performance and foreign language anxiety, and the potential moderating effect of personality traits. A survey was administered to 200 EFL Chinese students, and the data were analyzed using descriptive analyses, correlation analyses, and regression analyses. Descriptive analyses showed a moderate level of anxiety and oral presentation performance reported by students, and female students reported a higher level of anxiety. Furthermore, correlation analyses revealed the negative association between self-perceived oral presentation performance and foreign language anxiety. Among the 15 items of oral presentation performance, fluency and confidence displayed the highest negative correlation with foreign language anxiety. More importantly, hierarchical regression analyses confirmed that extraversion and openness had negative moderating effects on the correlation between self-rated oral presentation performance and foreign language anxiety. This research ends with pedagogical implications regarding greater focus on oral presentation skills, positive reinforcement to students, and attention to individual personality differences.